Microbial regulation of offspring diseases mediated by maternal-associated microbial metabolites - Jiang, Qingru; Li, Tian; Chen, Wei; Huo, Yingfang; Mou, Xiangyu; Zhao, Wenjing (Frontiers in Microbiology, 2022)
The microbiota plays a crucial role in individuals’ early and long-term health. Previous studies indicated that the microbial regulation of health may start before birth. As the in utero environment is (nearly) sterile, the regulation is probably be originated from maternal microbiota and mediated by their metabolites transferred across the placenta. After the birth, various metabolites are continuously delivered to offspring through human milk feeding. Meanwhile, some components, for example, human milk oligosaccharides, in human milk can only be fermented by microbes, which brings beneficial effects on offspring health. Hence, we speculated that human milk-derived metabolites may also play roles in microbial regulation. However, reports between maternal-associated microbial metabolites and offspring diseases are still lacking and sparsely distributed in several fields. Also, the definition of the maternal-associated microbial metabolite is still unclear. Thus, it would be beneficial to comb through the current knowledge of these metabolites related to diseases for assisting our goals of early prediction, early diagnosis, early prevention, or early treatment through actions only on mothers. Therefore, this review aims to present studies showing how researchers came to the path of investigating these metabolites and then to present studies linking them to the development of offspring asthma, type 1 diabetes mellitus, food allergy, neonatal necrotizing enterocolitis, or autism spectrum disorder. Potential English articles were collected from PubMed by searching terms of disease(s), maternal, and a list of microbial metabolites. Articles published within 5 years were preferred.